(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Arsenic tops the list of priority list of hazardous substances 2022. People are frequently exposed to the environmental pollutant metalloid arsenic through their food, water, air, and soil. Arsenic is famous for its toxic effects. However, arsenicals have recently gained attention due to promising clinical trials for the treatment of acute myeloid leukemia. Presently numerous studies on arsenic’s anticancer effects have been done. So a review was conducted on the use of arsenicals as poison and medicine. Arsenical was used as a powerful medicine in the BC era. But arsenical became famous as "the King’s Poison" and "the Poison of the King" due to its use as poison. But the development of Marsh’s Test in the 18th century led to a decrease in the use of arsenicals as poison. In the 18th century, arsenicals were used as medicine to treat a variety of diseases such as fever, rheumatism, psoriasis, and syphilis. The development of antibiotics, new, safer chemotherapeutic agents, and radiotherapy halted its use as medicine. The dose and form of arsenicals make them medicine or poison. Many literary works reveal that arsenic’s journey as “medicine” and “poison” is still ongoing in the twenty-first century.